The role of systematics for understanding ecosystem functions: Proceedings of the Zoologica Scripta Symposium, Oslo, Norway, 25 August 2022. (7th March 2023) - Bachmann, Lutz; Beermann, Jan; Brey, Thomas; de Boer, Hugo J.; Dannheim, Jennifer; Edvardsen, Bente; Ericson, Per G. P.; Holston, Kevin C.; Johansson, Veronika A.; Kloss, Paul; Konijnenberg, Rebecca; Osborn, Karen J.; et al.
Abstract: On 25 August 2022, the Zoologica Scripta ‐ An International Journal of Systematic Zoology and the Norwegian Academy of Sciences and Letters arranged a symposium entitled 'The role of systematics for understanding ecosystem functions' in the Academy's premises in Oslo, Norway. The symposium aimed at offering a forum for exploring and discussing trends and future developments in the field of systematics. Eleven international experts contributed expertise on various issues related to global challenges, such as biodiversity assessments, databases, cutting‐edge analysis tools, and the consequences of the taxonomic impediment. Here, we compiled a multi‐author proceedings paper of the symposium contributions that are arranged in chapters and presents the content and the key conclusions of the majority of the presentations.